CPW fed WLAN monopole antenna with gain improvement - Mat Zaid, A. F. (Elsevier B.V., 2016)
Monopole antennas have been widely used in the telecommunication industry in recent years. Most of the monopole antennas are designed to operate at Wireless Local Area Network (WLAN) application which has the advantage of unlicensed Industrial, Scientific, Medical (ISM) bands. ISM bands include of IEEE 802.11 a/b/g WLAN standards which have different speed data rates and operating frequency. The current issue stated that people always complain about their WiFi's signal coverage which is normally low. In an effort to solve this coverage problem, improvement must be made on the antenna's gain. A conventional gain of a monopole antenna operated at 2.4 GHz is normally 2 dBi. A coplanar waveguide (CPW) fed WLAN monopole antenna which is operated at 2.4 GHz with gain improvement is designed. In this project, the gain is improved by using the parasitic element technique. The concept is based on the Yagi-Uda antenna which consists of reflector and directors. The simulated and measured gain achieved is 6.9 dBi and 7.9 dBi respectively. Hence, the gain increment is 5.9 dBi if compared to the conventional gain. The designed antenna produced a directional radiation pattern which covers almost 90°of the antenna's coverage area.